2008
DOI: 10.2190/pm.38.3.a
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Visceral Fat and Adrenal Gland Volume in Women with Depression: Preliminary Results of a Morphometric Mri Study

Abstract: The increase of adrenal volume and VAT and the correlation of BDI with VAT in the upper abdomen support the hypothesis of long-term production of stress hormones in depression. This study is a further step toward describing morphologic substrates of depression in endocrine organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
(22 reference statements)
2
22
0
Order By: Relevance
“…This same group performed a prospective trial involving 48 adolescents without psychiatric illness and 48 adolescents with parental history of depression and found that elevated nocturnal urine free cortisol at baseline was associated with development of depression at follow-up [5]. A recent study also confirmed the presence of greater adrenal gland volume, measured by MRI, in 10 depressed women compared with 12 healthy women [6].…”
Section: Association Of Depressed Mood With Hpa Axis Functionmentioning
confidence: 92%
See 1 more Smart Citation
“…This same group performed a prospective trial involving 48 adolescents without psychiatric illness and 48 adolescents with parental history of depression and found that elevated nocturnal urine free cortisol at baseline was associated with development of depression at follow-up [5]. A recent study also confirmed the presence of greater adrenal gland volume, measured by MRI, in 10 depressed women compared with 12 healthy women [6].…”
Section: Association Of Depressed Mood With Hpa Axis Functionmentioning
confidence: 92%
“…1 Outline of potential biologic mechanism by which depression predisposes toward development of diabetes. HPA-hypothalamicpituitary-adrenal; SNS-sympathetic nervous system Rao et al [5] ↑ Urine free cortisol associated with development of depression Ludescher et al [6] ↑ Adrenal gland volume in depressed…”
Section: Hpa Axis Hyperactivity Catecholaminesmentioning
confidence: 99%
“…In light of the close association of adrenal gland size with body surface area [13] and body mass index [14], it appears to be appropriate to normalize urinary glucocorticoid metabolite excretion rates for measures of body size. Correction for differences in lean body mass by calculating the ratio of daily glucocorticoid excretion rates to urine creatinine, an established surrogate parameter of muscle mass, resulted in similar cortisol production rates in obese and non-obese adult subjects [9,15].…”
Section: Influence Of Lean Body Mass On Glucocorticoid Excretionmentioning
confidence: 99%
“…In detail, enlarged adrenal gland volume has been found in three case-control studies (Kessing et al, 2011), and most although not all cross-sectional studies have reported increased volumes of intra-abdominal adipose tissue in patients with major depression using imaging technology (Eskandari et al, 2005;Everson-Rose et al, 2009;Greggersen et al, 2011;Kim et al, 2011a,b;Krishnamurthy et al, 2008;Ludescher et al, 2008;Weber-Hamann et al, 2002;Williams et al, 2009). One study reported increased PAT in depression so far .…”
Section: Introductionmentioning
confidence: 96%
“…Ludescher et al (2008) studied 10 patients with MDD using MRI and found increased volumes of IAT in depression, and a correlation with adrenal volume. In a study with 22 postmenopausal women with major depressive disorder (MDD) using MRI Weber-Hamann et al (2002) found elevated volumes of IAT only in the hypercortisolemic subgroup.…”
Section: Introductionmentioning
confidence: 99%